1999
DOI: 10.2307/177250
|View full text |Cite
|
Sign up to set email alerts
|

Forest Response to Catastrophic Wind: Results from an Experimental Hurricane

Abstract: Abstract. Infrequent, intense wind disturbance is an important factor in northeastern U.S. forests, yet little is known about the early stages of vegetation reorganization, or the processes that facilitate biotic regulation of ecosystem function after such storms. We designed an experiment, based on a simulated hurricane blowdown, to examine the relationship of tree damage patterns to mortality and regeneration, community dynamics, vegetation recovery, and ecosystem processes. In October 1990, selected canopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 7 publications
4
45
1
Order By: Relevance
“…Thus, the understory fern community in the LEF is more resistant and resilient to hurricane effects than is the woody plant community. Although future research is needed, the high resilience of the understory fern community may enact some inhibitory effects on the recruitment and establishment of woody plant species (Royo and Carson, 2006), as previously observed with the temperate fern, Dennstaedtia punctilobula, that increased 100% in cover after the experimental blowdown study at the Harvard Forest LTER site (Cooper-Ellis et al, 1999), and with the tree fern Cyathea arborea, and scrambling ferns in the Gleicheniaceae on landslide scars in the LEF (Walker et al, 2010).…”
Section: Population and Community Attributesmentioning
confidence: 80%
See 3 more Smart Citations
“…Thus, the understory fern community in the LEF is more resistant and resilient to hurricane effects than is the woody plant community. Although future research is needed, the high resilience of the understory fern community may enact some inhibitory effects on the recruitment and establishment of woody plant species (Royo and Carson, 2006), as previously observed with the temperate fern, Dennstaedtia punctilobula, that increased 100% in cover after the experimental blowdown study at the Harvard Forest LTER site (Cooper-Ellis et al, 1999), and with the tree fern Cyathea arborea, and scrambling ferns in the Gleicheniaceae on landslide scars in the LEF (Walker et al, 2010).…”
Section: Population and Community Attributesmentioning
confidence: 80%
“…A similar result was found in the Harvard Forest blowdown study, where saplings and sprouts increased fourfold, including early successional species such as Betula spp. (Carlton and Bazzaz, 1998;Cooper-Ellis et al, 1999). Community analysis in the CTE demonstrated that the dominant individuals in the small size classes of the trimmed plots were pioneer species, and the establishment of pioneers in the canopy trimmed plots (3-6 new species on average) resulted in significant increases in woody plant species richness relative to intact canopy plots (Zimmerman et al, 2014).…”
Section: Population and Community Attributesmentioning
confidence: 98%
See 2 more Smart Citations
“…Species richness and diversity of ground beetles were higher in salvaged gaps following severe wind disturbance (>70% tree mortality) [61], and activity-abundance was higher in salvaged gaps following wildfire [122]. Koivula and Spence [123] reported increased activity-abundance and species richness with increasing salvage logging intensity (low: 23-30% timber removed, moderate: Severe wind storms generally fell a high proportion of canopy trees forming large, patchy gaps, although some trees lose only branches and remain standing [96]. Tipped trees form pits and mounds that mix organic and mineral layers, expose rocks and roots, and create distinct microsites that differ from neighboring undisturbed soil [97][98][99][100][101].…”
Section: Windmentioning
confidence: 99%